PEMODELAN DAN PERAMALAN INDEKS HARGA SAHAM GABUNGAN (IHSG), JAKARTA ISLAMIC INDEX (JII), DAN HARGA MINYAK DUNIA BRENT CRUDE OIL MENGGUNAKAN METODE VECTOR AUTOREGRESSIVE EXOGENOUS (VARX) - Nunung Hanurowati; Moch. Abdul Mukid; Alan Prahutama (Jurnal Gaussian, 2016)
Index of stocks listed on the Indonesia Stock Exchange (IDX) there are conventional that one of them is the Composite Stock Price Index (CSPI) and the index of stocks that are sharia is the Jakarta Islamic Index (JII). In its movement, the value of CSPI and JII often increases and decreases that are influenced by several factors, one of which is the world oil price of Brent Crude Oil. To see the value of CSPI and JII conditions during the period of the next few months it takes the model equations. Because the third such data included in the time series data, we used time series analysis with the appropriate method is the Vector Autoregressive Exogenous (VARX). VARX(p,q) is a model of multivariate time series that consists of several endogenous variable of the time series order p with q adding exogenous variables. The purpose of this study is to obtain an appropriate VARX models and forecasting for data CSPI and JII. The model to predict CSPI and JII with exogenous variables that influence the world oil prices of Brent Crude Oil is VARX(1,1). Test parameters for exogenous variables in the model VARX(1,1) not significant at significance level α = 5%, but this result could be ignored and continues to testing residual assumptions. Residual model VARX(1,1) satisfies the assumption of white noise and multivariate normal distribution, in order to obtain results as very good forecast that with each MAPE value for CSPI and JII forecast of 2,71% and 3,63%. Keywords: CPSI, JII, Brent Crude Oil, VARX, MAPE.